Polymorphisms in the FKBP5 gene region modulate recovery from psychosocial stress in healthy controls - Ising, Marcus; Depping, Anna-Mareike; Siebertz, Anna; Lucae, Susanne; Unschuld, Paul G.; Kloiber, Stefan; Horstmann, Sonja; Uhr, Manfred; Müller-Myhsok, Bertram; Holsboer, Florian (The European journal of neuroscience, 2008)
Mood and anxiety disorders are considered stress‐related diseases characterized by an impaired function of mineralocorticoid and glucocorticoid receptors (MR and GR, respectively), the major regulatory elements of the hypothalamus–pituitary–adrenocortical (HPA) axis. A number of so‐called chaperone proteins moderate the function of these receptors. Genetic variations in one of these chaperones, FKBP5, were associated with antidepressant treatment response in depression and with a major risk‐factor for the development of posttraumatic stress disorder. To further investigate the effect of FKPB5 polymorphisms on corticosteroid receptor‐mediated HPA axis regulation we conducted the Trier Social Stress test, a standardized procedure to evaluate psychosocial stress response, in 64 healthy volunteers. We genotyped rs4713916, rs1360780 and rs3800737, the three single nucleotide polymorphisms (SNPs) in the FKBP5 region which had shown the strongest effect in previous studies. In addition, we evaluated the effects of the GR polymorphisms Bcl1 and N363S as well as the MR polymorphism I180V. Subjects homozygous for any of the FKBP5 variants displayed an incomplete normalization of the stress‐elicited cortisol secretion. This was also observed following a second test additionally accompanied by an increased self‐reported anxiety. Regarding GR and MR, only carriers of the Bcl1 variant displayed an altered cortisol response in the prognosticated direction. While Bcl1 was predominantly associated with anticipatory cortisol, homozygous carriers of the FKBP5 minor allele showed insufficient cortisol recovery and increased self‐reported anxiety after psychosocial stress. This reaction pattern suggests that subjects carrying these variants are at risk of displaying chronically elevated cortisol levels after repeated stress constituting a risk factor for stress‐related diseases.